Impaired Glucose Metabolism in Young Offspring of Female Rats with Hypothyroidism - Zhoujun Liu; Yu Chen; Guofang Chen; Xiaodong Mao; Xiao Wei; Xingjia Li; Yijiao Xu; Fan Jiang; Kun Wang; Chao Liu (Journal of Diabetes Research)
Purpose. Because thyroid hormones from the maternal thyroid glands are known to influence the growth, development, and metabolic functioning of offspring, we used a rat model to preliminarily investigate the effects of maternal hypothyroidism on glucose metabolism, pancreas cell proliferation, and insulin production in young male offspring and the possible underlying mechanisms. Methods. Female rats were divided into a maternal hypothyroidism (MH) group, which received water containing 0.02% 6-propyl-2-thiouracil before and during pregnancy to induce hypothyroidism, and a control group which consumed tap water. Results. Our results showed that there were no differences of islets structure between the offspring from the two groups, but glucose metabolism was impaired with higher plasma glucose concentrations at 0 and 15 min in the OGTT in 8-week-old offspring of the MH group. From birth to 8 weeks, pancreatic TRβ1 and TRβ2 mRNA level declined significantly in MH offspring, accompanied by decreased Ki67 and insulin mRNA expression. Conclusions. Maternal hypothyroidism results in impaired pancreatic insulin synthesis and pancreatic cell proliferation in neonatal offspring and subsequent glucose intolerance in young offspring, which may be related to TRβ gene downregulation in the pancreas.